Bidirectional interactions along the microbiota–gut–brain axis in radiation-induced brain injury: mechanisms and therapeutic insights - Yuan, Yayi; Wang, Nan; Ning, Kang; Dang, Xuhong (Frontiers in Oncology, 2026)
Radiation therapy is widely used for the treatment of brain tumors and metastases from extracranial malignancies; however, it may also cause damage to normal brain tissue, potentially resulting in radiation-induced brain injury (RBI). Emerging evidence highlights the microbiota–gut–brain axis (MGBA) as a critical mediator of bidirectional communication between the gut microbiota and the brain, playing an important role in central nervous system (CNS) homeostasis and pathology. This review aims to summarize current evidence regarding the potential involvement of the MGBA in the pathogenic mechanisms of RBI, with particular emphasis on bidirectional interactions along this axis. We focus on underlying mechanisms, including neuroimmune and inflammatory responses, signal transduction, DNA damage, and oxidative stress. By integrating these perspectives, this review seeks to provide a novel conceptual framework for understanding RBI and to identify potential directions for future MGBA-targeted interventions.